2021
DOI: 10.18203/2394-6040.ijcmph20210820
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional survey to assess the knowledge, attitude, practice about COVID-19 among bystanders of patients visiting OPD, AIIMS, New-Delhi, India

Abstract: Background: According to WHO, the prevention and control of an epidemic and pandemic constitutes following preventive measures like hand washing, cough etiquette and dissemination of knowledge among other measures. In context to COVID-19, these measures have been proved to be very effective rendering various countries to be free of COVID-19. The knowledge, attitude and practice studies play an important role in assessing the societal readiness to accept behavioural changes, moreover they also determine baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…12 Chowdhury et al study also revealed a significant positive correlation (r=0.263) between knowledge and practice scores. 13 This study revealed a significant association between knowledge score regarding COVID-19 and education level as well as job status too. Our study findings are supported by the study Lee et al where they revealed that level of knowledge varied by sociodemographic characteristics.…”
Section: Discussionmentioning
confidence: 56%
“…12 Chowdhury et al study also revealed a significant positive correlation (r=0.263) between knowledge and practice scores. 13 This study revealed a significant association between knowledge score regarding COVID-19 and education level as well as job status too. Our study findings are supported by the study Lee et al where they revealed that level of knowledge varied by sociodemographic characteristics.…”
Section: Discussionmentioning
confidence: 56%